Traffic Management Review Of Passenger And Vehicle In Kariangau Ferry Port, East Kalimantan Province - Mir Akmam Noor Rashid; Paulina M Latuheru; Dio Deski Putra Maros (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2019)
Kariangau Ferry Port is one of the ferry ports located in the province of East Kalimantan. At this time in the harbor is a lot of people and vehicles who are not interested can enter the territory of the port causes the port to be less orderly asintroduction / pickup entering the harbor area, the crossing at some point due to the lack of supporting facilities such as signs and road markings. This occurs due to the lack of zoning in accordance with the Regulation of the Minister of Transportation Number 29 of 2016 on Sterilization Harbor. In order to ease the flow of traffic both incoming and out of the harbor area by implementing a zoning system based regulation Number 29 of 2016 concerning sterilization ferry ports and regulate traffic flow Seaport Crossing by the Director General of Land Transportation Regulation Number SK.242 / HK. gangway for passengers Then the addition of amenities such as signs, weigh bridge, road markers in order to become a regular port.